Serum IL-18 level, clinical symptoms and IL-18-607A/C polymorphism among chronic patients with schizophrenia in a Chinese Han population. (June 2016) - Zhang, Xiang Yang; Tan, Yun-Long; Chen, Da-Chun; Tan, Shu-Ping; Malouta, Michelle Z.; Bernard, Jared D.; Combs, Jessica L.; Bhatti, Sarai; Davis, Michael C.; Kosten, Thomas R.; Soares, Jair C.
Highlights: 772 patients and 775 controls were compared for IL-18 level and its -607A/C polymorphism. No significant differences in the allele and genotype frequencies between the patients and controls. Increased IL-18 and it polymorphism were associated with the PANSS total and G subscale scores. Association of IL-18 with clinical symptoms was present only among patients carrying the C allele. Abstract: Literature suggests that alterations in the inflammatory and immune systems are involved in the pathogenesis of schizophrenia. Specifically, patients diagnosed with schizophrenia exhibit increased IL-18, a pleiotropic proinflammatory cytokine in type 1 T-helper (Th1) responses. The functional 607A/C promoter polymorphism of the IL - 18 gene is also associated with the psychopathology of this disorder. However, no current study has explored its role in the clinical symptoms of schizophrenia as mediated through IL-18 levels. We recruited 772 inpatients with schizophrenia and 775 healthy controls in a Han Chinese population and genotyped the IL - 18 -607A/C polymorphism. Patient psychopathology was assessed using the Positive and Negative Syndrome Scale (PANSS). Serum IL-18 levels were measured in 80 patients and 93 healthy controls. Our results showed that there were no significant differences in the distribution of the allele and genotype frequencies between the patients and controls. Both increased IL-18 serum level and the IL - 18 -607A/C polymorphism were positively associated with the PANSS general psychopathology subscore and the PANSS total score. Moreover, interaction of increased IL-18 serum level and the IL - 18 -607A/C polymorphism influenced the clinical psychopathological symptoms, indicating that association of IL-18 level with the PANSS general psychopathology subscale or the total scores was present only among patients carrying the C allele. We demonstrate an association between the IL - 18 -607A/C variant and clinical psychopathological symptoms in schizophrenia. Findings suggest that the association between higher IL-18 levels and clinical symptoms in schizophrenia is dependent on the IL - 18 -607A/C polymorphism.